Democracia, políticas públicas e instituiç\~oes de deliberaç\~ao participativa: Vis\~oes sobre a experiência brasileira - Sandro Pereira Silva (Instituto de Pesquisa Econômica Aplicada (IPEA), 2018)
– This paper was based on some previously delimited categories to guide a reflexive debate about the production on the institutionalized social participation in the scope of the public administration in Brazil. To that end, the analytical course was organized and developed around a new concept for a generic definition of these innovations in the field of democratic practice in the country, here called "participatory deliberation institutions" (PDI), each with its particular functional characteristics. For a better operationalization of this concept, the text is ordered from three analytical pairs: i) institutionalization and structural insertion of these innovations; ii) participation and representativeness; and iii) deliberation and effectiveness. On these pairs some arguments in the literature have been embedded and problematized in order to shed light on different issues that fall within this highly complex field, aiming also for a more precise detailing of the central characteristics in terms of the democratic advances and intrinsic contradictions found dispersed in the area debate. With this, it is believed that this text makes a relevant contribution to the mapping of the "master lines" of analysis on a field of practices that, despite the rich production already existing, still makes possible and even lacks other exploratory investigations, given the dynamism inherent in the very process of democratic consolidation.
Keywords: Z18; 330; participatory deliberation institutions; social participation; participatory democracy; socio-state interfaces; political project